EFL Students' Views of the Multicultural Education in an Indonesian Islamic Higher Education - Shafa Shafa (Dinamika Ilmu, 2022)
Education cannot be separated from culture. It is possible to provide learning and be tolerant of other cultures. Multicultural education offers diverse cultures, ethnicity, and religion. The study aims to explore students' views of multicultural education in learning at an Indonesian Islamic higher education. It employs a descriptive study by applying a quantitative approach. By considering the ethnic and study program, respondents in this study were determined through the purposive sampling technique by involving 25 students from the Faculty of Tarbiyah and Teacher Training UINSI Samarinda, each representing five different study programs in the faculty. They enrolled as Ma’had Al-Jami’ah students obligated to study English in their initial semester. They were chosen from various study programs because they came from different ethnic backgrounds. This study collects data with a questionnaire instrument distributed online through a Google Forms. Descriptive statistics were used to tabulate and present the quantitative data collected from the questionnaire. The findings in this study provide an overview of the different perspectives of students at Islamic higher education on multicultural education in their learning. This study groups students' views of multicultural education in learning at Islamic higher education into three categories, (1) Highly Supportive on Multicultural Education, (2) Moderately Supportive on Multicultural Education, and (3) Lowly Supportive on Multicultural Education. Most of them have understood the values of multicultural education and are very supportive of its implementation in every lecture and campus policy but there are still students who do not understand the values of this multicultural education. Continuous studies are necessary to support the application of this multicultural education from time to time according to the needs of each institution.